Analisis Karakteristik Busur Api Listrik Pada Tegangan Rendah Arus Searah (DC) Dipengaruhi Oleh Resistansi Konduktor - Anjar Bryantiko Pangestu; Faiz Husnayain; Amien Rahardjo (Website, 2020)
Arc faults are a fire-safety risk in both AC (alternating current) and DC wiring, but reliable detection of arc faults and determining the appropriate response is particularly difficult in DC plug-load circuits. This study will discuss the impact of impedance on arc interference characteristics in DC low voltage systems. Experiments were conducted involving accidents that increasingly occur using the arc chamber as a means of experimenting with independent variables including cable cross-sectional area and the number of fibers and control variables will consist of currents and voltages using devices using a Picoscope. In the analysis obtained values of the conductor resistance affect the characteristics of electric arcs. The smaller the value of the conductor resistance, the greater the value of the arc current produced. This is consistent with the values obtained from the study, when the smallest conductor resistance of 0.036 Ω obtained the highest value at the current value and electric arc power of 20.57 A and 19.43 W at the cross section of the conductor 1.5 mm2 with 24 fibers.